2007
DOI: 10.1021/ja0740925
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Equilibria of Cis/Trans Isomerization of Backbone Amide Bonds in Peptoids

Abstract: The biological activities of N-substituted glycine oligomers (peptoids) have been the subject of extensive research. As compared to peptides, both the cis and trans conformations of the backbone amide bonds of peptoids can be significantly populated. Thus, peptoids are mixtures of configurational isomers, with the number of isomers increasing by a factor of 2 with each additional monomer residue. Here we report the results of a study of the kinetics and equilibria of cis/trans isomerization of the amide bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(147 citation statements)
references
References 33 publications
5
138
0
Order By: Relevance
“…In our study all atoms of the system were considered explicitly. The simulation results obtained by GROMOS force field have been found to be in good agreement with the experimental results on β peptides and peptoids [26,27,52]. The Dundee-PRODRG2 server [53] was used to obtain the GROMACS topology and coordinate files.…”
Section: Methodssupporting
confidence: 70%
See 2 more Smart Citations
“…In our study all atoms of the system were considered explicitly. The simulation results obtained by GROMOS force field have been found to be in good agreement with the experimental results on β peptides and peptoids [26,27,52]. The Dundee-PRODRG2 server [53] was used to obtain the GROMACS topology and coordinate files.…”
Section: Methodssupporting
confidence: 70%
“…Peptoids are generally synthesized by coupling a haloacetic acid and a primary amine by using DMF or DMSO as solvents [25]. Due to the hydrophobic nature of peptoids compared to the corresponding amino acids they are difficult to crystallize and their structural studies have mainly been carried out by circular dichroism-a low resolution technique and NMR spectroscopy [23,[26][27][28][29][30][31]. Also, crystallographic studies are mostly on cyclic peptoids and there are only a few studies on linear peptoids [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, both molecules have shown interesting biological properties as inhibitors of the formation of the apoptosome. [21, 27a] The main feature in the By considering previous studies on peptoids and the identity of the 1 H NMR signals that were split more significantly, [16] we proposed the cis/trans isomerization around the exocyclic tertiary amide bond to be the dynamic process responsible for this conformational behavior (Scheme 3).…”
Section: Structure Of the Conformationally Constrained Peptidomimeticmentioning
confidence: 98%
“…By taking advantage of the intensive research into short peptoids as a result of their potential application in drug discovery, Borchardt and Rabenstein recently reported the use of NMR spectroscopic techniques to study cis/trans isomerization by rotation around the amide bonds of small peptoid models. [16] These authors observed a slow cis/trans exchange rate for even the most labile of the amide bonds between the two C-terminal residues. This feature can be of importance with respect to the on/off rates for the ligand/receptor binding or when facing undesired interactions with other targets.…”
Section: Introductionmentioning
confidence: 99%